(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This study examines the possible methods for lps sexdentatus Boerner control in the more general context of integrated protection of woodland areas. In consequence of the fire this bark beetle showed important gradations in the Natural Reserve of Monte Alpe (Lombardy, Northern ltaly). According to biological observations, carried out in 1991-92 at different altitudes (800-1200 m), the species accomplished 3 flights; the first during May-June, the second in August, and the third in October. The research focused on the identification of some components of the pheromonic mixture, and on the possibility of using attraction substances to stimulate the aggregation effect. The «radiator» traps demonstrated a greater effect than the «tube» traps in attracting the Scolitidae. Pheromone baited tree-trunks showed the same level of efficacy as the «radiator» traps, and a much higher efficacy to that of tree-trunk traps without pheromone. The (+) α-phellandren-8-ol and (-) α-phellandren-8-ol were tested to evaluate the attraction of I. sexdentatus. The new molecules when used alone do not have an attractive effect, but when used in combination with racemic ipsdienols have a synergic effect.